Perancangan Aplikasi Penitipan Hewan (Dog Hotel) Berbasis Web Menggunakan Metode Extreme Programming (Studi Kasus: CV. Bintang Lima) - Fajar Santoso; Munawaroh (Journal of Research and Publication Innovation, 2023)
The Animal Boarding Application (Dog's Hotel) is a system designed for employees to manage animal boarding data using web-based technology and the Extreme Programming methodology. The aim of this research is to design and implement an efficient and effective animal boarding data processing application for employees. The Extreme Programming methodology was chosen for the development of this application due to its ability to adapt to changing software development needs. Before proceeding with the application design phase, an analysis of the animal boarding data processing requirements was conducted to understand the design objectives. The design phase involved the creation of a database structure, user interface, and application workflow. The application was developed using PHP programming language, CodeIgniter 3 framework, JavaScript, and MySQL database. The user interface was designed using HTML, CSS, and Bootstrap 4 framework. The application provides features for users, both employees and administrators, to manage animal boarding data, search for pet owners' information, schedule boarding appointments, and provide manifest information for pet pick-up and drop-off. The application has been successfully tested and meets the requirements of employees, offering an effective solution for animal boarding data management.